Single Dose of SHR-1222, a Sclerostin Monoclonal Antibody, in Healthy Men and Postmenopausal Women With Low Bone Mass: A Randomized, Double-Blind, Placebo-Controlled, Dose-Escalation, Phase I Study - Dai, Zhijie; Fang, Pingfei; Yan, Xiang; Zhu, Ronghua; Feng, Qiong; Yan, Qiangyong; Yang, Lingfeng; Fan, Xiao; Xie, Yuting; Zhuang, Lihong; Feng, Sheng; Liu, Yantao; et al. (Frontiers in Pharmacology, 2021)
SHR-1222 is a humanized monoclonal antibody targeting sclerostin and has the potential to promote bone formation and reduce bone resorption. This study was aimed to assess the safety, tolerability, pharmacokinetics, pharmacodynamics, and immunogenicity of SHR-1222 in healthy men and postmenopausal women with low bone mass (BMD). It was a randomized, double-blind, placebo-controlled, dose-escalation, phase I study. Subjects received SHR-1222 at 50, 100, 200, 300, and 400 mg sequentially or matching placebo subcutaneously. Totally, 50 subjects with low BMD were enrolled and randomly assigned; 10 received placebo and 40 received SHR-1222 (50 mg, n=4; 100, 200, 300, or 400 mg, n=9). The most common adverse events that occurred at least 10% higher in subjects with SHR-1222 treatment than those with placebo were decreased blood calcium, blood urine present, increased blood cholesterol, electrocardiogram T wave abnormal, urinary tract infection, increased blood pressure diastolic, and positive bacterial test. All the above adverse events were mild in severity and well resolved except one of increased blood cholesterol in a subject lost to follow-up. The serum SHR-1222 concentration increased in a dose-dependent manner. Administration of SHR-1222 upregulated the bone-formation markers N-terminal propeptide of type 1 procollagen, osteocalcin, and bone-specific alkaline phosphatase, while downregulated the bone-resorption marker β-C-telopeptide. The BMD at the lumbar spine notably rose after a single dose of SHR-1222. The largest increase occurred in the 400 mg cohort (3.8%, 6.7%, and 6.1% on day 29, 57, and 85, respectively; compared with 1.4%, 0.8%, and 1.0% in the placebo group). Although 10.0% of subjects receiving SHR-1222 tested positive for anti–SHR-1222 antibodies, no obvious effects of antibody formation were found on pharmacokinetics. Overall, SHR-1222 was well tolerated at doses from 50 to 400 mg and is a promising new remedy for osteoporosis.